Mutational analysis and protein expression of PI3K/AKT pathway in four mucinous cystadenocarcinoma of the breast - Yan Zheng; Huaxiao Tang; Qian Liu; Yujie Zhang; Peng Zhao; Shukun Zhang; Chengqin Wang (Diagnostic Pathology)
Abstract Introduction Primary mucinous cystadenocarcinoma of the breast (BMCA) is a rare neoplasm with few reports in the literature. Its molecular characteristics, prognosis, and treatment protocols are not well understood, and there is a lack of consensus concerning the optimal management of this condition. Methods Four cases of clinical and pathological data were collected from 2018 to 2024. Next generation sequencing with a 654 cancer-associated gene panel was utilized to detect gene mutations. Immunohistochemistry was carried out to evaluate protein expression levels. Results Firstly, we combined clinical imaging examinations and IHC to exclude the possibility of metastasis from ovarian or pancreatic origins. BMCA was composed of cystically dilated ducts lined by tall columnar mucin-containing epithelium. The morphological spectrum of MCA varied from MCA alone to MCA combined with carcinoma in situ (CIS) to MCA associated with invasive ductal carcinoma (IDC). ER/PR/HER2 and CK20 were all negative, while CK7 and GATA3 were positive by IHC in four cases. Although the prognosis of the other three patients was favorable during the follow-up periods of 13, 10, and 3 months, respectively, case 2# experienced a recurrence of the primary focus after 42 months. No lymphatic metastasis was identified in cases 1–4#. In addition, next-generation sequencing (NGS) identified 17 mutated genes and 25 mutation sites in four cases. TP53, PIK3CA, AKT, PTEN, and RB1 were the highest frequency mutated genes. Given that AKT mutations typically refer to AKT1(E17K) rather than AKT2 or AKT3, AKT protein expression was detected only in Case 2# (AKT1, E17K). PTEN protein was expressed in case 4# (corresponded to missense mutation), loss of PTEN expression were corresponding with splicing mutation in case1#. In brief, AKT and PTEN protein expression could be corresponded to gene mutation in a certain extent. However, PIK3CA protein expression was positive in Case 2# but negative in Case 1#, which did not fully accordance with the NGS-detected missense mutations. No associated germline variations were detected. Additionally, neither PDL-1 expression nor microsatellite instability-high (MSI-H) status was identified. Conclusion The tumorigenesis and development of BMCA may be regulated to the PI3K/AKT pathway. Consequently, a comprehensive genetic analysis of more cases could elucidate the molecular mechanisms underlying this rare tumor.